2005
DOI: 10.1002/ijc.20893
|View full text |Cite
|
Sign up to set email alerts
|

Myxoid liposarcoma FUS‐DDIT3 fusion oncogene induces C/EBP β‐mediated interleukin 6 expression

Abstract: The myxoid/round cell liposarcoma oncogene FUS-DDIT3 is the result of a translocation derived gene fusion between the splicing factor FUS and DDIT3. In order to investigate the downstream targets of DDIT3, and the transforming effects of the FUS-DDIT3 fusion protein, we have introduced DDIT3-GFP and FUS-DDIT3-GFP constructs into a human fibrosarcoma cell line. The gene expression profiles of stable transfectants were compared to the original fibrosarcoma cell line by microarray analysis. We here report that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The NF-kB-controlled genes MMP1 and LCN2 are upregulated in FUS-DDIT3-expressing cell lines MMP1 and LCN2, both genes involved in extracellular matrix remodeling, were found to be upregulated in FUS-DDIT3-GFP cells, whereas DDIT3 had very little effect (Go¨ransson et al, 2005). The expression patterns were confirmed here by real-time PCR (Table 1).…”
Section: Physical Interaction Between Nfkbiz and Fus-ddit3supporting
confidence: 71%
See 1 more Smart Citation
“…The NF-kB-controlled genes MMP1 and LCN2 are upregulated in FUS-DDIT3-expressing cell lines MMP1 and LCN2, both genes involved in extracellular matrix remodeling, were found to be upregulated in FUS-DDIT3-GFP cells, whereas DDIT3 had very little effect (Go¨ransson et al, 2005). The expression patterns were confirmed here by real-time PCR (Table 1).…”
Section: Physical Interaction Between Nfkbiz and Fus-ddit3supporting
confidence: 71%
“…NF-kB is a major factor controlling IL8 transcription in FUS-DDIT3-expressing cells DDIT3 and FUS-DDIT3 give opposite effects on the IL8 transcription in HT1080 cells (Go¨ransson et al, 2005). To study the mechanism behind this difference, we expressed luciferase reporter constructs containing the C/EBP-NF-kB composite site of the IL8 promoter, or mutant forms of this construct in genetically modified HT1080 cells (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with those of studies in other human cancers, which have demonstrated that the main effect of C/EBPβ over-expression is induction of uncontrolled proliferation. 13,[21][22][23] Additionally, the role of several major NPM-ALK activated signaling pathways in C/EBPβ expression and activation was explored. Through the use of gene silencing experiments, we were able to dissect several mechanisms through which NPM-ALK exerts its control on C/EBPβ.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoadsorbed DNA was analyzed by PCR using the following primers: IL-6 promoter (5 ¶-AGCACTGGCAGCACAAGGCAAAC-3 ¶ and 5 ¶-CAAGCCTGGGATTAT-GAAGAAGG-3 ¶), Cyp1a1 enhancer (5 ¶-TAAGAGCCCCGCCCCGACTTCCT-3 ¶ and 5 ¶-TAGCTTGCGTGCGCCGGCGACAT-3 ¶). Cyp1a1 and IL-6 ChIP primers are previously published (25,26).…”
Section: Methodsmentioning
confidence: 99%